2020
DOI: 10.2478/sm-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Languages and Cultures in the Integration Process of Migrant and Local Communities

Abstract: SummaryThere is no denying that fact that migration is a sensitive economic, political and social issue, which European institutions together with researchers and policy makers have been working on trying to create the cohesion between migrant and host communities. It has been widely recognized that attitudes towards migrants tend to be more positive when migrants have an opportunity to reveal their linguistic and cultural diversity to non-migrants. Researchers claim that local governments and municipalities “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Research has shown that children raised in multilingual households may experience cognitive benefits such as enhanced creativity, problem-solving skills, and cognitive adaptability. The benefits stem from the unique linguistic and cultural encounters that multilingual youngsters are exposed to, which can enhance their cognitive development (From et al, 2022;Pundziuvienė et al, 2023;Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that children raised in multilingual households may experience cognitive benefits such as enhanced creativity, problem-solving skills, and cognitive adaptability. The benefits stem from the unique linguistic and cultural encounters that multilingual youngsters are exposed to, which can enhance their cognitive development (From et al, 2022;Pundziuvienė et al, 2023;Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%